Achieving high antimicrobial activity: Composite alginate hydrogel beads releasing activated charcoal with an immobilized active agent. (15th September 2018) - Osmokrovic, Andrea; Jancic, Ivan; Vunduk, Jovana; Petrovic, Predrag; Milenkovic, Marina; Obradovic, Bojana
Highlights: Composite alginate hydrogels were optimized to release activated carbon particles. Optimized formulation released AC particles over 5 days in physiological saline. Povidone iodine was strongly adsorbed onto AC particles within the hydrogel. Composites with PVP-I induced strong bactericidal effects without PVP-I desorption. Composites are attractive for wound treatments avoiding iodine side effects. Abstract: New composites based on Ca-alginate hydrogels were produced that release activated charcoal (AC) particles with adsorbed povidone iodine (PVP-I) as a model antimicrobial substance in a physiological-like environment. Composite beads with different alginate (0.5–1.5%w/w) and AC (1–20%w/w) concentrations were analyzed by FE-SEM and characterized regarding textural parameters, swelling, and AC release kinetics. PVP-I was easily adsorbed onto AC particles within the optimized beads (0.5%w/w alginate, 20%w/w AC) as indicated by UV–vis spectroscopy, EDX and FT-IR analyses. The obtained beads have shown strong bactericidal effects against two standard bacterial strains ( Staphylococcus aureus and Pseudomonas aeruginosa ) and clinical multi-resistant wound isolates ( MRSA, Escherichia coli, Pseudomonas aeruginosa, Еnterococcus faecalis and Proteus mirabilis ) and, at the same time, exhibited negligible PVP-I desorption in physiological saline solution. Thus, the obtained composites could provide utilization of potent antiseptics such as iodine, in wound dressings, without the concern of systemic absorption.